DINAMIKA INTERAKSI SOSIAL PADA PERKEMBANGAN ANAK MADRASAH IBTIDAIYAH DI ERA 4.0 - Nurkhairina (STKIP Subang, 2026)
The Industrial Revolution 4.0 has brought significant changes to various aspects of life,including the social interaction patterns of children. Students at Madrasah Ibtidaiyah (Islamic elementary schools), as part of the digital generation, have experienced a shift in their modes of interaction—from traditional face-to-face communication to more digitally mediated forms. This shift impacts their social and emotional development, including a decline in interpersonal communication skills, empathy, and the ability to build healthy social relationships. This article aims to examine the dynamics of social interaction among Madrasah Ibtidaiyah students in the context of the digital era, as well as the critical roles played by teachers and parents in balancing digital and conventional social interactions. Using a descriptive qualitative approach, this study concludes that proper guidance and a supportive learning environment are essential to fostering children’s social development amidst the challenges of modern technology.